2019
DOI: 10.1111/sji.12734
|View full text |Cite
|
Sign up to set email alerts
|

Role of arginine deiminase in thymic atrophy during experimental Streptococcus pyogenes infection

Abstract: Expression of gene of arginine deiminase (AD) allows adaptation of Streptococcus pyogenes to adverse environmental conditions. AD activity can lead to L‐arginine deficiency in the host cells’ microenvironment. Bioavailability of L‐arginine is an important factor regulating the functions of the immune cells in mammals. By introducing a mutation into S pyogenes M46‐16, we obtained a strain with inactivated arcA/sagp gene (M49‐16 delArcA), deficient in AD. This allowed elucidating the function of AD in pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…Opposite, arginine depletion could be manifested later, when the bacterial load and AD output in the site of pathogen invasion dramatically increase. In our previous research, using murine model of streptococcal infection we found a gradual arginine decrease in blood showing the lowest values on the fifth day of postinfection [26].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Opposite, arginine depletion could be manifested later, when the bacterial load and AD output in the site of pathogen invasion dramatically increase. In our previous research, using murine model of streptococcal infection we found a gradual arginine decrease in blood showing the lowest values on the fifth day of postinfection [26].…”
Section: Discussionmentioning
confidence: 76%
“…The study was carried out with S. pyogenes M49-16 isogenic mutant lacking the ability to make AD that has been constructed and characterized earlier [27]. An assay SDSCs prepared from the parental and mutant strains showed that significant AD activity was present in parental SDSC but none could be detected in mutant one [26]. It was established that parental and mutant strains SDSC did not exhibit toxic impact on human PBMCs (Tabl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that L-arginine is an important regulator of the mTOR signaling pathway (124), which is essential for the development of T cells (125). Based on this theory, a Russian team found that Streptococcus pyogenes infection could induce thymic atrophy in mice and confirmed that this atrophy was inextricably associated with the reduction of L-arginine in the bloodstream by arginine deiminase produced by Streptococcus pyogenes (75). In fact, many pathogens that cause thymic atrophy can express products that reduce L-arginine in the blood (126).…”
Section: Streptococcusmentioning
confidence: 99%
“…Истощение L-аргинина может являться одним из элементов стратегии патогена, направленной на ограничение или дисрегуляцию иммунных реакций, поэтому АД может рассматриваться как фактор патогенности, способствующий выживанию и персистированию патогена. Ранее в наших исследованиях была показана зависимость активности диссеминации S. pyogenes от их способности продуцировать АД [47]. Влияние АД на развитие воспаления в ходе инфекционного процесса до сих пор слабо изучено.…”
Section: Introductionunclassified